PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN ETIKA SUKARELA - Sindy Lolita Sinaga; Herry Laksito (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the influence of audit committee characteristics on voluntary ethics disclosure. The independent used in this study are expertise of audit committee members, frequency of meeting of audit committee, audit committee size, audit committee tenure and multiple directorships of audit committee members while the dependent variable used in this study is voluntary ethics disclosure. The population in this study consists of all companies listed on the Indonesian Stock Exchange in 2018. Sample of this study is obtained by using purposive sampling method and there are 90 samples that fulfill the criteria. This study uses a multiple regression analysis. The results of this study indicate that only two audit committee characteristics that is frequency of meeting and multiple directorship were significantly related with the voluntary ethics disclosure, while expertise, size and tenure were not significantly related with the voluntary ethics disclosure.